Peningkatan Keterampilan Lansia Tentang Pengendalian Hipertensi Dengan Relaksasi Otot Progresif - Arif Hendra Kusuma; Meita Rahmawati; Ayu Puji Lestari (JPS : Jurnal Pengabdian Serulingmas, 2023)
Hypertension has become a public health problem and will become a bigger problem if it is not treated early. Management of hypertension can be done with pharmacological and non-pharmacological therapy. Several complementary treatments have been found to help lower blood pressure, one of which is progressive muscle relaxation. Efforts to change a continuous maintenance behavior one of which is by providing health education. Community service activities in the form of health education and improving hypertension control skills with progressive muscle relaxation. The purpose of this activity is to increase the knowledge and skills of the elderly in controlling hypertension with progressive muscle relaxation. The method used in this community service is health education about controlling hypertension with progressive muscle relaxation and demonstrations of progressive muscle relaxation. The target in this activity is the elderly Posyandu participants in Kalipomahan Hamlet, Kalikudi Village, totaling 22 people. The results of the activity are an increase in the knowledge and skills of the elderly in controlling hypertension with progressive muscle relaxation.